Digital Libraries Advancing Open Science - Vancauwenbergh, Sadia (IntechOpen, 2021)
Over the past decades, traditional academic library environments have transformed into digital libraries. This has resulted in many challenges for libraries in terms of the reinvention of libraries' roles and organizations, the skill sets of librarians, and library infrastructure. At the same time, this profound transformation has opened the door to many new avenues, such as the support and advancement of Open Science. This book offers insights into the transformation of traditional library environments to digital libraries and details how digital libraries can contribute to Open Science, in particular to Open Access, FAIR and Open Data, and Open Education, by describing methods, criteria, strengths, and weaknesses as well as applications.